45-day mortality after 467,779 knee replacements for osteoarthritis from the National Joint Registry for England and Wales: an observational study. - Hunt, L; Ben-Shlomo, Y; Clark, E; Dieppe, P; Judge, A; MacGregor, A; Tobias, J; Vernon, K; Blom, A (Lancet, 2014)
BACKGROUND: Understanding the risk factors for early death after knee replacement could help to reduce the risk of mortality after this procedure. We assessed secular trends in death within 45 days of knee replacement for osteoarthritis in England and Wales, with the aim of investigating whether any change that we recorded could be explained by alterations in modifiable perioperative factors. METHODS: We took data for knee replacements done for osteoarthritis in England and Wales between April 1, 2003, and Dec 31, 2011, from the National Joint Registry for England and Wales. Patient identifiers were used to link these data to the national mortality database and the Hospital Episode Statistics database to obtain details of death, sociodemographics, and comorbidity. We assessed mortality within 45 days by Kaplan-Meier analysis and assessed the role of patient and treatment factors by Cox proportional hazards models. FINDINGS: 467,779 primary knee replacements were done to treat osteoarthritis during 9 years. 1183 patients died within 45 days of surgery, with a substantial secular decrease in mortality from 0·37% in 2003 to 0·20% in 2011, even after adjustment for age, sex, and comorbidity. The use of unicompartmental knee replacement was associated with substantially lower mortality than was total knee replacement (hazard ratio [HR] 0·32, 95% CI 0·19–0·54, p<0·0005). Several comorbidities were associated with increased mortality: myocardial infarction (HR 3·46, 95% CI 2·81–4·14, p<0·0005), cerebrovascular disease (3·35, 2·7–4·14, p<0·0005), moderate/severe liver disease (7·2, 3·93–13·21, p<0·0005), and renal disease (2·18, 1·76–2·69, p<0·0005). Modifiable perioperative risk factors, including surgical approach and thromboprophylaxis were not associated with mortality. INTERPRETATION: Postoperative mortality after knee replacement has fallen substantially between 2003 and 2011. Efforts to further reduce mortality should concentrate more on older patients, those who are male and those with specific comorbidities, such as myocardial infarction, cerebrovascular disease, liver disease, and renal disease. FUNDING: National Joint Registry for England and Wales.